Highly efficient semitransparent perovskite solar cells for four terminal perovskite-silicon tandems - Dewi, Herlina Arianita (2020)
Tandem solar cells (SCs) based on perovskite and silicon represent an exciting possibility for a breakthrough in photovoltaics, enhancing SC power conversion efficiency (PCE) beyond the single-junction limit while keeping the production cost low. A critical aspect to push the tandem PCE close to its theoretical limit is the development of high-performing semitransparent perovskite top cells, which also allow suitable near-infrared transmission. Here, we have developed highly efficient semitransparent perovskite SCs (PSCs) based on both mesoporous and planar architectures, employing Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3 and FA0.87Cs0.13PbI2Br perovskites with band gaps of 1.58 and 1.72 eV, respectively, which achieved PCEs well above 17 and 14% by detailed control of the deposition methods, thickness, and optical transparency of the interlayers and the semitransparent electrode. By combining our champion 1.58 eV PSCs (PCE of 17.7%) with an industrial-relevant low-cost n-type Si SCs, a four-terminal (4T) tandem efficiency of 25.5% has been achieved. Moreover, for the first time, 4T tandem SCs’ performances have been measured in the low light intensity regime, achieving a PCE of 26.6%, corresponding to revealing a relative improvement above 9% compared to the standard 1 sun illumination condition. These results are very promising for their implementation under field-operating conditions.